The Influence of Demographic Heterogeneity on the Emergence and Consequences of Cooperative Norms in Work Teams - Chatman, Jennifer A.; Flynn, Francis J. (Academy of Management Journal, 2001)
Drawing from social categorization theory, we found that greater demographic heterogeneity led to group norms emphasizing lower cooperation among student teams and officers from ten business units of a financial services firm. This effect faded over time. Perceptions of team norms among those more demographically different from their work group changed more, becoming more cooperative, as a function of contact with other members. Finally, cooperative norms mediated the relationship between group composition and work outcomes.